2008
DOI: 10.1080/03615260801970774
|View full text |Cite
|
Sign up to set email alerts
|

The “80/20 Rule” and Core Journals

Abstract: This column examines the 80/20 rule, also termed a Pareto distribution, and explains these terms' historical origins. The column focuses on this pattern in the use of print serials, downloads from electronic databases, and citations to journals. The rule's relationship to Bradford's Law is explored, and some of the research pertaining to the 80/20 rule is reviewed. The pattern's utility for defining the core collection and serials collection management is discussed, whereas a number of limitations are pointed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 15 publications
1
43
1
3
Order By: Relevance
“…Competing interests (e.g., research vs. teaching vs. service) pose a challenge to promoting innovation in education and encouraging scholarship. Further, the dissemination of scholarship has its own challenges, with only a small subset of journals that accept descriptive/innovation articles and journal reviewers setting high expectations (80/20) [17,18]. …”
Section: The Challenge: Empowering Medical Educators’ Scholarshipmentioning
confidence: 99%
“…Competing interests (e.g., research vs. teaching vs. service) pose a challenge to promoting innovation in education and encouraging scholarship. Further, the dissemination of scholarship has its own challenges, with only a small subset of journals that accept descriptive/innovation articles and journal reviewers setting high expectations (80/20) [17,18]. …”
Section: The Challenge: Empowering Medical Educators’ Scholarshipmentioning
confidence: 99%
“…This graph brings to mind the Pareto Principle, also known as the 80/20 rule or the principle of uneven distribution, where a subset of users are disproportionately productive. 42 This general principle of uneven or unequal distribution is the underlying premise for many laws in bibliometrics including Bradford's Law. However, Bradford's Law applies primarily to serials and was discovered through bibliographic analysis, whereas the 80/20 rule's application to libraries was discovered by studying use patterns.…”
Section: Interlibrary Loan Usersmentioning
confidence: 99%
“…More recently, Singson and Hangsing (2015) observed the same trend in usage of electronic journals across an academic consortium in India. Nisonger (2008) provides many more examples.…”
Section: Commentarymentioning
confidence: 99%
“…Trueswell (1969b) noted that heavily used books would need new book cards more frequently, perhaps leading to the destruction of the full cards prior to tabulation, and many librarians are familiar with "helpful" patrons who reshelve their own materials after using them in-house, resulting in under-reporting this use. Nisonger (2008) summarized an extensive, but not comprehensive, selection of studies that reported on the 80/20 Rule. In a subset of 19 articles reporting on the concentration of titles in print serials usage, Nisonger (2008) showed that most approximated the 80/20 Rule but noted that "the 80/20 numbers are not expected to work out precisely" (p. 65).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation